Biomechanical Modelling of the Upper Limb for Robotics-Based Orthotic Tremor Suppression - E. Rocon; A. F. Ruiz; J. L. Pons (Applied Bionics and Biomechanics)
Orthotic management has been proposed as an interesting alternative to current tremor management methods. It is expected that an improvement on manipulative function can be obtained by reducing the tremorous motion associated with some neurological disorders. For this to be possible, a sound modelling of the tremor and the biomechanical characteristics of the upper limb is required. This paper proposes a model for both the tremor motion and the biomechanical parameters of the upper limb. Based on these models and on a prototype of a robotics-based active orthosis two tremor reduction strategies are proposed.